2009
DOI: 10.1111/j.1471-6712.2008.00674.x
|View full text |Cite
|
Sign up to set email alerts
|

The representation of healthcare end users’ perspectives by surrogates in healthcare decisions: a literature review

Abstract: This systematic review has revealed that the involvement of surrogates is an additional vital way to represent end users' perspectives in healthcare decisions where for a range of reasons their opinions are unable to be effectively ascertained. However, because of the heterogeneity of surrogates and end users, the selection of appropriate surrogates and deploying surrogate decisions require particularly careful consideration of their value in individual cases; thus, subsequent decision-making must be reviewed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 55 publications
1
9
0
Order By: Relevance
“…The use of surrogates in the WEB study is consistent with the findings of Shah and Robinson (5) in terms of acting on behalf of the device users, without losing sight of the fact that users should have the final say on the design and presentation of the novel devices. In the MATCH literature review by Bridgelal Ram et al (11) a short report was identified which illustrates clearly the negative effects of not involving end users appropriately in both design and purchasing.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…The use of surrogates in the WEB study is consistent with the findings of Shah and Robinson (5) in terms of acting on behalf of the device users, without losing sight of the fact that users should have the final say on the design and presentation of the novel devices. In the MATCH literature review by Bridgelal Ram et al (11) a short report was identified which illustrates clearly the negative effects of not involving end users appropriately in both design and purchasing.…”
Section: Discussionsupporting
confidence: 82%
“…However, certain obstacles arose which resulted in the use of surrogates (principally the research assistant on the project and the designer). The definition of a ‘surrogate’ adopted in the study follows those identified in a literature review by Shah and Robinson (5) who support the use of surrogates as a potentially useful approach to ascertaining end user requirements, whilst also advocating a critical case by case approach to ensure that end users interests are best served in the process. Surrogates were defined therein as any healthcare professional and/or caregiver who acts formally on behalf of the healthcare end user concerning the end user's health care.…”
Section: Introductionmentioning
confidence: 99%
“…1315,17,21,22,2426,28,29,31,32,34–36,3841,4345,4863,66,69,70,74,7680,8284,8690,92 The studies reviewed were from a variety of international settings: United States (n = 33); United Kingdom (n = 7); France (n = 5); the Netherlands (n = 5); Spain (n = 3); and Canada, Sweden, Finland, Germany, Switzerland, Turkey, Hong Kong, Scotland, Norway, Italy, South Africa, Israel, Korea, Austria, and Nigeria. Investigators in 29 studies discussed consent in patients with only medical conditions, 29 in patients with cognitive impairments only, and 19 in patients with both medical and cognitive issues or frail or vulnerable elderly (eTable 1, available online at the end of this article).…”
Section: Resultsmentioning
confidence: 99%
“…Investigators rarely discussed these concepts as important issues affecting patient treatment during a dental emergency. Although investigators in some articles addressed issues arising from a conflict of interest between a patient with a medical or cognitive condition and his or her surrogate or proxy, 55,72,74 there were no articles in which the investigators discussed these issues in the geriatric dentistry literature. Overall, in our review we found a paucity of articles discussing the topic of informed consent in geriatric dentistry.…”
Section: Discussionmentioning
confidence: 99%
“…This situation gives rise to a potential imbalance of power associated with individual capacities such as communication skills, health literacy, self-confidence, and emotional investment in decisions, and therefore intra and interpersonal conflict when discerning patients’ best interests. 11 , 14 …”
Section: Discussionmentioning
confidence: 99%